Σεμνός and its Cognates in the Sophoclean Scholia - Easterling, Patricia E. (Hyperboreus, 2015)
This note explores the possible implications of σεμνός, σεμνῶς and τὸ σεμνόν in scholia on Sophocles (OC 1547–1548, 1606, 712–715; Ajax 492–493; OT 264) which discuss the effects of particular words, allusions or types of phrase.